1975
DOI: 10.1007/bf00445024
|View full text |Cite
|
Sign up to set email alerts
|

Biological age and habitual physical activity in relation to physical fitness in 12-and 13-year-old schoolboys

Abstract: Ile purpose of this study »as to imcstigatc the relationship het « ecu biological age. habitual physical activity and aul liropomet I'ical and physiological charactei'isties in 12-and Ki-year-old schoolboys (n 7(1). Mi'1/iiiil.i. At the beginning and the end of the school year 1971/72 biological age «as determined by measuring skeletal age (Vom left hand N-ray photographs. Habitual physical activity «as determined by quest ionnaire interview and pedometers. lii'fuill«: All anthropométrie:!] characterist ies sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The results, however, were restricted to a specific sample: only boys in the age range 12 13 years. There were also indications that differences in biological development and in habitual physical activity of the pupils could have masked any effects (27). The relatively good physical performance capacity of these boys may have caused the absence of positive training effects.…”
mentioning
confidence: 98%
“…The results, however, were restricted to a specific sample: only boys in the age range 12 13 years. There were also indications that differences in biological development and in habitual physical activity of the pupils could have masked any effects (27). The relatively good physical performance capacity of these boys may have caused the absence of positive training effects.…”
mentioning
confidence: 98%
“…In most of the boys' fat variables, slopes and intercepts were significantly different between active and non-active individuals. TRIC is the only skinfold that increases despite the activity factor (Kemper et al, 1975). Knechtle et al (2012) revealed that TRIC skinfolds were not reduced during exercise in adult ultramarathon runners.…”
Section: Resultsmentioning
confidence: 91%
“…If attached to the waist of the subject, it registers vertical displacements of the center of gravity. We used the totalized pedometer score over a given period of time as a measure of habitual physical activity (2). A previous study (1) showed that the actual step rate has a common regression with oxygen uptake in walking as well as in running.…”
Section: Introductionmentioning
confidence: 99%